Hubungan Disiplin Belajar dan Minat Belajar dengan Hasil Belajar Pendidikan Agama Islam pada Materi Kebebasan Mengemukakan Pendapat Siswa Kelas VII di MTs Negeri 1 Sidoarjo Kabupaten Sidoarjo - Ahmad Ahmad (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2020)
This study aims to determine the relationship of learning discipline and learning interest with learning outcomes of islamic religious education. This study uses a survey method, namely: research conducted on large and small populations, but the data studied is sample data taken from the population, so it is found relative events, distribution, and relationships between sociological and psychological variables